EFFECT OF RENAL DENERVATION ON OFFICE BLOOD PRESSURE IN PATIENTS WITH UNCONTROLLED HYPERTENSION: A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED, SHAM-CONTROLLED TRIALS. (April 2021) - Stavropoulos, Konstantinos; Imprialos, Konstantinos; Patoulias, Dimitrios; Katsimardou, Alexandra; Koutsampasopoulos, Konstantinos; Alataki, Sofia; Kerpiniotis, Georgios; Dimitriadis, Kyriakos; Papademetriou, Vassilios; Tsioufis, Konstantinos; Doumas, Michael
Abstract : Objective: Untreated and uncontrolled hypertension remain a significant global health problem and a major cardiovascular risk factor. The role of renal denervation (RDN) in the treatment of hypertension has been studied extensively at basic and clinical research level during the last decade. We aimed to provide precise effects estimates about the effect of RDN on office blood pressure levels in patients with untreated or uncontrolled hypertension. Design and method: PubMed and CENTRAL, along with grey literature sources, were searched from their inception to May 2019 for randomized, sham-controlled trials evaluating the efficacy and safety of RDN on the management of hypertension, irrespective of study blinding, setting and sample size. Results: Six randomized, sham-controlled trials were identified and included in the meta-analysis. In total, 981 patients with hypertension were randomized in all 6 trials to undergo either RDN (n = 585) or sham-procedure (n = 396). Compared to sham, RDN resulted in a significant decrease in office systolic blood pressure levels by 5.47 mmHg (95% CI: -8.10 to -2.84; I^2 = 0%) and in office diastolic blood pressure levels by 4.25 mmHg (95% CI: -6.16 to -2.33; I^2 = 0%), compared to sham procedure. No major safety issues were detected. Conclusions: RDN is associated with a significant reduction in both systolic and diastolic office blood pressure levels, confirming its promising role in the field of hypertension treatment.